Development of a motivational regulatory strategy scale for Indonesian learners of Japanese - Yamashita, Junko (Frontiers in Psychology, 2023)
Opportunities for LOTE (Language Other Than English) to engage with their target language are limited, making it challenging to sustain motivation. The aim of this study is to develop and validate a scale for measuring motivational regulatory strategies among Japanese-language learners and investigate its relationship with motivational factors. This research focuses on Indonesian learners of Japanese with non-Kanji (Chinese characters) background and are studying Japanese as a foreign language. The motivational regulatory strategies scale comprises six factors and has demonstrated adequate internal consistency and factor structure. The findings indicate a positive correlation between integrative motivation and these six strategies, suggesting that learners' integrative motivation may promote the adoption of these strategies. Furthermore, it emphasizes the significance of opportunity control strategy, where learners actively seek chances to expose themselves to their target language. Future research is recommended to implement the developed scale in educational settings. Conducting surveys that encompass learners from diverse cultural backgrounds and embarking on longitudinal studies should also be considered.